2021
DOI: 10.3390/biom11101506
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of the Role of Metalloproteinases in the Pathogenesis of Autoimmune Pemphigus and Pemphigoid

Abstract: Pemphigus and pemphigoid diseases are potentially life-threatening autoimmune blistering disorders that are characterized by intraepithelial and subepithelial blister formation, respectively. In both disease groups, skin and/or mucosal blistering develop as a result of a disruption of intercellular adhesion (pemphigus) and cell-extracellular matrix (ECM) adhesion (pemphigoid). Given that metalloproteinases can target cell adhesion molecules, the purpose of the present study was to investigate the role of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 54 publications
(48 reference statements)
0
13
0
1
Order By: Relevance
“…These cells contain and release upon activation dozens of cytokines, chemokines, hydrolytic degrading enzymes, including matrix metalloprotease 9 (MMP9) and neutrophil elastase, as well reactive oxygen species. This inflammatory cascade ultimately leads to tissue damage and subepidermal blister formation (17)(18)(19)(20)(21).…”
Section: Pathogenesis Of Bullous Pemphigoidmentioning
confidence: 99%
“…These cells contain and release upon activation dozens of cytokines, chemokines, hydrolytic degrading enzymes, including matrix metalloprotease 9 (MMP9) and neutrophil elastase, as well reactive oxygen species. This inflammatory cascade ultimately leads to tissue damage and subepidermal blister formation (17)(18)(19)(20)(21).…”
Section: Pathogenesis Of Bullous Pemphigoidmentioning
confidence: 99%
“…Since molecules related to metalloproteinases such as ADAM5, ADAM10, ADAM15 and ADAM17, can affect cell adhesion ( 8 ) and ADAM10 and ADAM17 are involved in the turnover of Dsg2 ( 17 , 24 , 31 ), we investigated the effects of ADAM10 and ADAM17 on intercellular adhesion of keratinocytes using specific inhibitors. First, we performed dispase-based dissociation assays to analyze the intercellular adhesion of immortalized murine (MEK) and human (HaCaT) as well as primary human (NHEK) epidermal keratinocytes ( Figures 1A, B ).…”
Section: Resultsmentioning
confidence: 99%
“…Beside direct inhibition of the interaction of demosomal cadherins, the antibody binding has been shown to trigger intercellular signaling pathways, which indirectly result in loss of desmoglein-mediated interaction and thus intraepidermal blistering. Kinases such as p38MAPK, PLC, ERK, and Src are activated by autoantibody binding and contribute to alterations of the keratin cytoskeleton and desmoglein internalization (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Nevertheless, the exact mechanisms causing blisters are not fully understood, yet.…”
Section: Introductionmentioning
confidence: 99%
“…The administration of anti-FasL antibodies after PVIgG injection blocks blister formation in wild-type mice, and mice lacking secreted soluble FasL develop a milder disease upon PVIgG injection [ 32 ]. Similarly, we have shown that MMP-9 is overexpressed in both in vivo and in vitro models of PV [ 33 ] and that MMP inhibition is a promising route to non-immunosuppressive PV treatment [ 34 ].…”
Section: Discussionmentioning
confidence: 99%